ANALISA MODERASI LITERASI KEUANGAN PADA HASRAT KONSUMTIF DAN FAKTOR LINGKUNGAN TERHADAP PERILAKU KEUANGAN PENGGUNA E-COMMERCE - Herlina Herlina; Fuji Rahayu Wilujeng (Institut Teknologi Nasional Malang, 2026)
Financial behavior is an individual's ability to manage finances effectively and wisely. Financial behavior is influenced by various factors, such as consumptive desire, environmental factors, and environmental literacy. The development of digital lifestyles and current social influences has led individuals to become more consumptive in carrying out financial activities. The low ability of individuals to manage finances properly is caused by high consumptive desires and the influence of the social environment, as well as the suboptimal role of environmental literacy in shaping financial behavior. This study aims to analyze the influence of desire and environmental factors on financial behavior and to examine the role of environmental literacy as an intervening variable. This study uses a quantitative approach with a survey method through the distribution of questionnaires to respondents. Data analysis techniques use regression analysis and mediation tests to determine the direct and indirect effects among the research variables. The results show that partially and simultaneously, desire and environmental factors have a positive and significant effect on financial behavior. Financial literacy as a moderating variable is unable to moderate the influence of desire on financial behavior, but it is able to moderate the influence of environmental factors on financial behavior.